What if Biological Asset Accounting Policies are linked to Tax Avoidance and Supply Chain Management? - Retno Martanti Endah Lestari; Wahyudin Zarkasyi; Ida Farida (International Journal of Supply Chain Management, 2020)
Tax management is carried out by all companies, including the agricultural sector. In practice, the impact on financial performance caused by various problems relates to accounting policies of biological assets, transparency, accountability, responsibility, independence, fairness, and the size of the company. This study aims to prove empirically whether there is an influence of biological asset accounting policy implications, good corporate governance practices, and company size on tax management through financial performance in agricultural sector companies. Supply chain management significantly and positively mediates among the relationship between policy implications, company size, good corporate governance practices, tax management and financial performance. Research data were collected through questionnaire instruments, face-to-face interviews, and group discussion forums, which were conducted in several places in Indonesia. Sampling was conducted with non-probability sampling. Data were analyzed using Structural Equation Model (SEM). The results showed that the implications of biological asset accounting policies and good corporate governance practices had a direct or indirect effect on tax management and financial performance. But company size has no direct or indirect effect on tax management and financial performance. The limitation of this research lies in the analysis unit of the plantation and forestry sector alone, not yet in other agricultural sectors such as livestock and fisheries that have the same characteristics as regulated in PSAK No. 69 Agriculture, namely biological transformation.